2014
DOI: 10.1186/2251-6581-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spent turmeric on kidney glycoconjugates in streptozotocin-induced diabetic rats

Abstract: BackgroundCurcumin known to have number of medicinal use and masked the fiber containing ukonan like active polysaccharide in turmeric and its pharmacological effect will be addressed on diabetic nephropathy particularly the glycoconjugates of extracellular components viz., glycoproteins and glycosaminoglycans - heparan sulfate (HS).MethodsMale Wistar rats were maintained on AIN-76 diet containing 10% spent turmeric and were grouped into control and STZ induced diabetes SFC/TFC and SFD/TFD, respectively. Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Therefore, we hypothesized that Tan IIA may be associated with the suppression According to a previous study, over-expression of TGF-β1 contributed to collagen deposition and GBM thickening. 28 Additionally, TGF-β1 can mediate tubulointerstitial fibrosis and renal hypertrophy in DN. 29 Our results showed that the diabetic state enhanced renal TGF-β1 expression, which is consistent with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that Tan IIA may be associated with the suppression According to a previous study, over-expression of TGF-β1 contributed to collagen deposition and GBM thickening. 28 Additionally, TGF-β1 can mediate tubulointerstitial fibrosis and renal hypertrophy in DN. 29 Our results showed that the diabetic state enhanced renal TGF-β1 expression, which is consistent with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged hyperglycemia is known to impair kidney function and structure [ 16 , 17 ]. Early pathological changes in DN include kidney enlargement, thickening of glomerular and tubular basement membranes, and increased urine albumin excretion rate [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] The utilization of e-GAGs by microbes through fermentation was confirmed using the well-established dye binding method (DMMB), which is very specific for GAGs. 51 The results showed a decreased content of e-GAGs, suggesting their utilization by microbes for their growth.…”
Section: Food and Function Papermentioning
confidence: 93%